Pengaruh Electronic Word of Mouth Melalui Media Sosial Tiktok Terhadap Minat Beli Produk Kosmetik Somethinc pada Mahasiswi di Jakarta - Jenny Sista Siregar; Dwi Atmanto; Winny Asri Deviana (EduInovasi: Journal of Basic Educational Studies, 2024)
The cosmetic brand Somethinc has achieved various milestones since 2019. However, some of its products still experience low sales. To remain competitive, Somethinc needs to develop an effective marketing strategy, with electronic word of mouth on TikTok potentially serving as a solution. This study aims to assess the impact of electronic word of mouth through TikTok on the purchase intention of Somethinc products among female students in Jakarta. This research employs a quantitative approach, combining survey and observational methods, with data collected through a questionnaire. The results reveal a t-test significance value of 0.000 (p < 0.05) and a t-value of 12.121, which exceeds the critical value of 1.984, confirming the rejection of the null hypothesis and the acceptance of the alternative hypothesis. These findings indicate a significant effect of electronic word of mouth through TikTok on the purchase intention of Somethinc products. The coefficient of determination (R-squared) is 0.600, meaning that electronic word of mouth through TikTok accounts for 60% of the variance in purchase intention for Somethinc products, while the remaining 40% is influenced by other variables not examined in this study.